2009
DOI: 10.1073/pnas.0906522106
|View full text |Cite
|
Sign up to set email alerts
|

The selective antagonist EPPTB reveals TAAR1-mediated regulatory mechanisms in dopaminergic neurons of the mesolimbic system

Abstract: Trace amine-associated receptor 1 (TAAR1) is a G protein-coupled receptor (GPCR) that is nonselectively activated by endogenous metabolites of amino acids. TAAR1 is considered a promising drug target for the treatment of psychiatric and neurodegenerative disorders. However, no selective ligand to identify TAAR1-specific signaling mechanisms is available yet. Here we report a selective TAAR1 antagonist, EPPTB, and characterize its physiological effects at dopamine (DA) neurons of the ventral tegmental area (VTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
301
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(320 citation statements)
references
References 31 publications
16
301
2
1
Order By: Relevance
“…The reduction of TAAR1 stimulation on DA terminals of VTA DA neurons, caused by decrease of striatal trace amine synthesis, may increase the firing frequency of VTA DA neurons [30,32]. This may lead to the increase of DA release in the nucleus accumbens, that is, mesolimbic DA hyperactivity.…”
Section: A New "D-cell Hypothesis" Of Schizophrenia (Figure 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of TAAR1 stimulation on DA terminals of VTA DA neurons, caused by decrease of striatal trace amine synthesis, may increase the firing frequency of VTA DA neurons [30,32]. This may lead to the increase of DA release in the nucleus accumbens, that is, mesolimbic DA hyperactivity.…”
Section: A New "D-cell Hypothesis" Of Schizophrenia (Figure 2)mentioning
confidence: 99%
“…It was clarified that increased stimulation of TAAR1 receptors on cell membranes of DA neurons in the midbrain ventral tegmental area (VTA) reduces firing frequency of VTA DA neurons [30][31][32].…”
Section: Trace Amine-associated Receptor Type 1 (Taar1)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that TAAR1 has a thermoregulatory function [33]. It was clarified that increased stimulation of TAAR1 receptors on cell membranes of DA neurons in the midbrain ventral tegmental area (VTA) reduced firing frequency of VTA DA neurons [30][31][32].…”
Section: Trace Amine-associated Receptor Type 1 (Taar1)mentioning
confidence: 99%
“…The trace amine-associated receptor, type 1 (TAAR1) having a large number of ligands, including tyramine, β-phenylethylamine (PEA) and psychostimulants, for example methamphetamine, 3,4-methylenedioxymethamphetamine (MDMA) and lysergic acid diethylamide (LSD) [23,25,29], has become a target receptor for exploring novel neuroleptics [30,31]. TAAR1 knockout mice showed schizophrenia-like behaviors with a deficit in prepulse inhibition [32].…”
Section: Trace Amine-associated Receptor Type 1 (Taar1)mentioning
confidence: 99%